Efficacy and safety of combination therapy with pirfenidone and nintedanib in patients with idiopathic pulmonary fibrosis - Huh, Jin-Young; Lee, Jae Ha; Song, Jin Woo (Frontiers in Pharmacology, 2023)
Background: Recent studies have suggested that combination therapy with pirfenidone and nintedanib is safe and tolerable in patients with idiopathic pulmonary fibrosis (IPF). However, data from real-world practice are limited. Thus, we aimed to investigate the safety and efficacy of this combination therapy in patients with IPF in a real-world setting. Methods: A multicenter retrospective cohort study was conducted to investigate the safety and efficacy of combination therapy with pirfenidone and nintedanib in 45 patients with IPF. Incidences of adverse events and rates of lung function decline were compared before and after the combination therapy. Propensity score matching was performed to compare the outcomes between the combination and monotherapy groups. Results: The mean age of the patients was 68.8 years, and 82.2% of them were male. The median follow-up duration after combination therapy was 12.1 months. The majority of the patients (97.8%) received nintedanib as an add-on to pirfenidone. The most common adverse events after the combination therapy were diarrhea and anorexia. Pirfenidone or nintedanib was stopped in 12 patients owing to gastrointestinal AEs, lung transplantation, or financial problems. In patients with serial lung function data, the rate of decline in the forced vital capacity was significantly reduced after the combination therapy. In the matched analysis, the combination group had a higher incidence of diarrhea than the monotherapy group without an increase in serious adverse events; however, the two groups had similar changes in forced vital capacity (FVC). Conclusions: The combination of pirfenidone and nintedanib in patients with IPF has the potential to reduce the rate of FVC decline. However, in the matched analysis, FVC decline was comparable between the patients on combination therapy and those on monotherapy. The incidence of certain adverse events, particularly diarrhea, was higher with combination therapy, but serious adverse events were similar between the groups.